PENDIDIKAN PRA NIKAH BAGI CALON PENGANTIN DI KUA KECAMATAN SYAMTALIRA BAYU - Cut Sukma Keumala; T. Amiruddin (Majelis Pendidikan Aceh, 2018)
Religious Affairs Office provides premarital guidance to prospective married couples wishing to marry. KUA has been trying to optimally provide premarital counseling. Recently, however, this ahir premarital guidance given KUA against the couple almost ignored. This is evident from past guidance in KUA that only lasts 1-2 hours, and is still very minimal. This is the reason that can be expressed by the authors as background research, entitled